Culture in Urban Development: Putting Forth the Hypothesis of a Bifurcation in France. - Sibertin-Blanc, Mariette (Taylor & Francis, 2020)
The relationship between cultural action and urban development has increasingly been analysed over the last two decades. Without dismissing the economic and urban renewal challenges supporting this dynamic, this article proposes to study another and yet decisive dimension of urban cultural action from the perspective of territorial development and management. It concerns a sensitive approach to urban development which values personal cognitive and emotional growth, individual emancipation and openness to the world through cultural and artistic practices. After presenting the changes in the paradigms of French local cultural action, the study focuses on various experiences undertaken in different urban areas (medium-sized cities and metropolis), showing a variety of strategies likely to foster this kind of urban development that goes beyond concerns for equipment and outreach. The vectors for such development, as well as the obstacles and resistance to change, are analysed, which helps understand why, although some evolutions are definitely present, they are still inconspicuous.
Keywords: Stadtentwicklung; Kultur; Stadtplanung; Planungsziel; Einflussfaktor; Integrierte Planung; Kulturangebot; Alltagskultur; Kulturpolitik; Kreatives Milieu; Kommunale Kulturpolitik